Analysis of the Role of Social Accounting in Addressing Income Inequality and Environmental Influences - Tahir, Arlan; Lande, Adriani; Ermawati, Yana; Basannang, Siti Mariani; Junaedy, Junaedy (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study examines the role of social accounting in addressing income inequality and managing environmental impacts, highlighting its adaptability across diverse socio-economic contexts and its contribution to corporate social responsibility (CSR). Utilizing a systematic literature review, this study synthesizes insights from recent research to explore how flexible social accounting frameworks align with different regulatory and socio-economic environments. It assesses both theoretical foundations and practical applications. Legitimacy theory serves as a conceptual basis, framing social accounting as a tool for building public trust and enhancing corporate accountability. The findings suggest that social accounting effectively promotes economic and environmental transparency. Social accounting fosters greater public trust and aligns corporate actions with societal expectations by enabling companies to record and report wage distribution, employment practices, and environmental metrics. The study also underscores the importance of flexible social accounting frameworks that allow companies to adapt to local socio-economic conditions, especially in regions with resource constraints or unique regulatory environments. This study advances the understanding of social accounting’s dual role as a reporting and strategic tool for sustainable development. Practically, it suggests that companies adopting adaptable social accounting frameworks can improve stakeholder relations, build credibility, and support long-term sustainability goals. These findings are relevant for corporate managers, policymakers, and future researchers interested in the impact of socially responsible practices on corporate reputation and public trust.